The responsibility of public authorities: comment on the Judgment 426/2020 of July 27, 2020 (Second Room of the Supreme Court) - Sarmiento Méndez, Xosé Antón (Journal of the Basque Parliament, 2021)
The scope of the principle of the interdiction of public powers is one of the essential issues for understanding the rule of law. In the case of the exercise of jurisdictional power, the impartiality of the courts becomes essential and reflection on their current practice is of interest to assess the democratic quality of a political system.